Examining Erythrocytes as Potential Blood Biomarkers for Autism Spectrum Disorder: Their Relationship to Symptom Severity and Adaptive Behavior - Tomas Jasenovec; Dominika Radosinska; Ivan Belica; Barbara Raskova; Angelika Puzserova; Norbert Vrbjar; Jana Radosinska (Biomedicines)
Background: Multiple research teams have documented various abnormalities in erythrocyte properties in children with autism spectrum disorder (ASD) compared with neurotypical individuals. Reduced erythrocyte deformability, a crucial factor for microcirculation and oxygen delivery, may affect brain function. Other key factors like nitric oxide (NO) and Na,K-ATPase-regulated cation transport also play roles in both erythrocyte deformability and ASD, suggesting a possible relationship between erythrocyte parameters and autism severity. Thus, this study aims to describe these associations, exploring erythrocyte properties as potential biomarkers in ASD. Methods: A total of 179 ASD children were enrolled in this study. Diagnosis was confirmed by the Autism Diagnostic Observation Schedule—Second Edition (ADOS-2) and Autism Diagnostic Interview-Revised. The Vineland Adaptive Behavior Scales, Third Edition (VABS-3), was used to assess adaptive behavior. RBC deformability was measured using a filtration technique, while NO production by RBCs was assessed via DAF-2DA fluorescence. Na,K-ATPase kinetics and RBC osmotic resistance were evaluated spectrophotometrically. Results: Children with more severe ASD symptoms had more impaired deformability and osmotic resistance than children with mild symptoms. Higher RBC NO production was linked to better scores in some VABS-3 subdomains, and in the social affect domain of ADOS-2. Higher affinity of Na,K-ATPase for sodium negatively correlated with the occurrence of repetitive and restricted behavior—one of the core ASD symptoms. Conclusions: This study identified potential links between ASD severity and RBC properties. While erythrocyte quality can influence ASD symptomatology, the observed relationships—such as those involving RBC deformability, NO production, Na,K-ATPase kinetics, and osmotic resistance—were not strong or consistent enough to be considered reliable diagnostic or prognostic biomarkers.